The state, public policy, and AIDS discourse - Adam, Barry D. (Contemporary crises, 1989)
The paper probes the "deep structure" of perceptions of AIDS and the ensuing public policy trends. AIDS has become the latest symbol indexing 20th century conflicts over the family and sexuality and recapitulates some features of early debates over contraception and the control of sexually transmitted diseases. From 1981 to 1983, public talk about AIDS was virtually taboo. Since 1983, the massive proliferation of AIDS discourse has led to the development of an "official story" common in the press and clear in the presumptions underlying recent state policies in the United States, Canada, and the United Kingdom. These policies have favored state control of sexual speech and education, as well as control of people "blamed" for HIV infection, while community-based groups have sought to empower people to affirm their sexuality while avoiding viral transmission.